2018
DOI: 10.1093/jn/nxx020
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Overfeeding with Dairy Cream Does Not Modify Gut Permeability, the Fecal Microbiota, or Glucose Metabolism in Young Healthy Men

Abstract: Our findings suggest that short-term overfeeding with an HFD does not significantly impair insulin sensitivity and gut permeability in normal-weight healthy men, and that changes in dominant communities of fecal bacteria occur only in certain individuals. The study was registered in the German Clinical Trial Register as DRKS00006211.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(40 citation statements)
references
References 56 publications
0
27
2
Order By: Relevance
“…The lack of community-level effects corroborates the few previous studies that have addressed effects of the type and quantity of dietary fat on the human microbiota in healthy subjects or general population. A 7-day overfeeding intervention with whipping cream (45E% of fat, mainly SAT) among 25 lean young German men did not yield consistent changes in the gut microbiota profiles [8]; similarly to a longer-term (18 weeks) moderate alteration in the intake of SAT (13e14 E% vs. 7e8 E%) in a multiethnic cohort with wide age and body mass index range [43]. Finally, no effects on beta diversity were observed after 8 weeks of omega-3 PUFA supplements in 22 healthy British volunteers [44].…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The lack of community-level effects corroborates the few previous studies that have addressed effects of the type and quantity of dietary fat on the human microbiota in healthy subjects or general population. A 7-day overfeeding intervention with whipping cream (45E% of fat, mainly SAT) among 25 lean young German men did not yield consistent changes in the gut microbiota profiles [8]; similarly to a longer-term (18 weeks) moderate alteration in the intake of SAT (13e14 E% vs. 7e8 E%) in a multiethnic cohort with wide age and body mass index range [43]. Finally, no effects on beta diversity were observed after 8 weeks of omega-3 PUFA supplements in 22 healthy British volunteers [44].…”
Section: Discussionmentioning
confidence: 84%
“…In addition, there is substantial heterogeneity in the methods used for clinical phenotyping and analysis of microbiota. Dietary intervention studies targeting the gut microbiota in humans in relation to NAFLD or other metabolic diseases have focused on either healthy, lean subjects [8] or obese subjects undergoing weight-loss programs [9e11]. No studies have examined effects of a hypercaloric intervention on gut microbiota in NAFLD in obese and overweight individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the modulation of some beneficial bacteria groups and not others might suggest the existence of cross-feeding mechanisms and confirm the influence of the initial gut microbiota composition before intervention in modulating the response to diet. In addition, the intake of a highly amount of dairy cream (source of LCFA) over 7 days did not affect bacterial diversity but did reduce Bacteroidetes and increased β-Proteobacteria levels [ 90 ]. As mentioned above, both the quantity and the quality of fat are relevant.…”
Section: Dietmentioning
confidence: 99%
“…There was no mention of an effect on Proteobacteria . In contrast, a small study consisting of healthy men fed a high-saturated-fat diet for 7 days reported an increase in Betaproteobacteria in a subset of individuals ( 19 ). Consumption of a high-fat diet (mixed fatty acids) by mice changes the fecal microbiome to raise the Firmicutes -to- Bacteroidetes ratio ( 39 ), while a diet high in saturated fats is associated with an increase in Proteobacteria ( 23 25 ).…”
Section: Observationmentioning
confidence: 94%
“…The most abundant members of the bacterial communities in human feces belong to the phyla Bacteroidetes and Firmicutes (18). Under conditions of high dietary saturated fat, a second taxon of Gram-negative organisms, Proteobacteria, is detected in human feces in some individuals (19), while in other studies they were not (20). This may be related to the amount of fat or the vulnerability of the individual exposed.…”
mentioning
confidence: 94%